Pinukuik Kulit Pisang: Optimasi Pemanfaatan Hasil Pertanian Pisang Kepok di Sumatera Barat - Gusti, Utari Akhir; Wildayati, Wildayati; Ardi, Ardi (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2024)
West Sumatra is known as one of the largest banana producers in Indonesia, yet this potential has not been fully optimized. If maximized, it could have a positive impact on the community. Additionally, West Sumatra is famous for its diverse cuisine, including Pinukuik, which is becoming increasingly rare due to the high cost of ingredients. This research introduces